Measuring Intraocular Pressure in Patients With Keratoconus With and Without Intrastromal Corneal Ring Segments. Issue 1 (January 2017) - Mendez-Hernandez, Carmen; Arribas-Pardo, Paula; Cuiña-Sardiña, Ricardo; Fernandez-Perez, Cristina; Mendez-Fernandez, Rosalia; Saenz-Frances, Federico; Benitez-del-Castillo, Jose M.; Garcia-Feijoo, Julian
Abstract : Purpose: To compare intraocular pressure (IOP) measurements made using 5 tonometers in keratoconic eyes with and without intrastromal corneal ring segments. Methods and Patients: This was an observational case series study. A total of 147 eyes of 147 patients with keratoconus, 74 of which had undergone corneal ring segment placement, were prospectively evaluated. IOP was measured using the tonometers Tonopen XL, Pascal dynamic contour tonometer, iCare Pro, ocular response analyzer (ORA), and Goldmann applanation (GAT) in random order. The Bland-Altman method was used to examine interinstrument agreement. Effects on readings of central corneal thickness, corneal curvature, and corneal astigmatism were assessed by multivariate regression analysis. Results: Smallest mean IOP differences with GAT measurements in eyes without and with ring segments, respectively, were detected for iCare Pro [0.2 (2.9) mm Hg and 0.4 (3.0) mm Hg, P =0.914] and greatest differences for ORA Goldmann-correlated IOP [5.8 (3.3) mm Hg and 6.0 (3.1) mm Hg, P =0.363]. Best agreement with GAT was shown by iCare Pro (ICC=0.829; 95% CI, 0.721-0.896) and worse agreement by ORA corneal-compensated IOP (ICC=−0.145; 95% CI, −0.826 to 0.283). All but the dynamic contour tonometer readings were influenced by central corneal thickness, yet these measurements were affected by the presence of ring segments ( P =0.017) and corneal astigmatism ( P =0.030). Corneal curvature only affected ORA Goldmann-correlated IOP ( P =0.029). Conclusions: All 5 tonometers provided reliable IOP readings in the keratoconic eyes regardless of the presence of corneal ring segments. iCare Pro readings were most consistent with GAT, whereas ORA readings were least consistent with this reference standard.